APLIKASI MODEL BISNIS MICROBANKING SYARIAH DI INDONESIA - Effendi, Jaenal; Baga, Lukman Mohammad; Beik, Irfan Syauqi; Nursyamsiah, Tita (IQTISHADIA, 2017)
Microbanking is generally defined as a broad set of financial services to meet the needs of the poor and small enterprises. However, mirobanking that have been well-designed might not have a positive impact on the poorest unless it particularly obtains to reach them through proper business model. On the other hand, Indonesia lists as the largest Moslem community in the world.  Hence, microbanking that are ruled under sharia regulation namely Islamic microbanking hopefully enable to support the development program particularly to the poor and SMEs in Indonesia. Therefore, the study of practices Islamic microbanking business model should be conducted in order to design the strategy of development, particularly on financial inclusion program. This study used qualitative analysis through a process of discussion, focus group discussion (FGD), in-depth interviews and literature review in order to gain information from primary and secondary sources as well as a comparative study of business models of Islamic microfinance in Indonesia.